Lipstick Evangelism: Avon Trading Circles and Gender Empowerment in South Africa - Dolan, C; Scott, L (2009)
Increasing numbers of corporations are vying to capture one of the largest untapped consumer markets – the world's poor – in ways that are not only economically profitable but socially responsible. One type of initiative that has gained increased traction is trading partnerships between multinational corporations and women's informal exchange networks, creating micro-enterprise opportunities that not only deliver soap and mobile phones, but financial empowerment for women. This article examines one such initiative – the trade in Avon cosmetics. It aims to determine the extent to which the initiative alleviates poverty, and fosters empowerment, among black women in South Africa. It suggests that as unlikely as cosmetics may seem as a vehicle for development, direct sales of beauty products can offer low risk opportunities for women to become entrepreneurs, and form a potentially promising route to gender-equitable poverty reduction.